Advertising Education at a Crossroad. (November 2019) - Lee, Sang Yeal
The changes in the advertising industry are rapid and dizzying. The advertising industry is going through structural change and advertising education faces a daunting challenge in keeping up with the real world. Advertising educators must recognize the urgency of revising the curriculum to address this challenge. If not, while the industry transitions into a different chapter, advertising education will be left behind. This article discusses major changes in the advertising industry, and calls for thought leadership to bridge the gap between academia and the industry and to initiate proactive changes in advertising education.